2009
DOI: 10.1186/1471-2164-10-75
|View full text |Cite
|
Sign up to set email alerts
|

Exploring and dissecting genome-wide gene expression responses of Penicillium chrysogenum to phenylacetic acid consumption and penicillinG production

Abstract: Background: Since the discovery of the antibacterial activity of penicillin by Fleming 80 years ago, improvements of penicillin titer were essentially achieved by classical strain improvement through mutagenesis and screening. The recent sequencing of Penicillium chrysogenum strain Wisconsin1255-54 and the availability of genomics tools such as DNA-microarray offer new perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 82 publications
(98 reference statements)
2
99
1
1
Order By: Relevance
“…Although P. chrysogenum cannot grow on phenylacetate as the sole carbon source, it can efficiently oxidize it (61). This ability has been severely reduced in modern production strains, which preferentially incorporate phenylacetate to penicillin G instead of catabolizing it (26,72). In contrast to the P. chrysogenum NRRL 1951 strain, which is the ancestor of modern penicillinproducing strain lineages, the model strain Wisconsin 54-1255, which represents an early stage in strain improvement, already exhibits the reduced consumption of phenylacetate and stable penicillin G production.…”
mentioning
confidence: 99%
“…Although P. chrysogenum cannot grow on phenylacetate as the sole carbon source, it can efficiently oxidize it (61). This ability has been severely reduced in modern production strains, which preferentially incorporate phenylacetate to penicillin G instead of catabolizing it (26,72). In contrast to the P. chrysogenum NRRL 1951 strain, which is the ancestor of modern penicillinproducing strain lineages, the model strain Wisconsin 54-1255, which represents an early stage in strain improvement, already exhibits the reduced consumption of phenylacetate and stable penicillin G production.…”
mentioning
confidence: 99%
“…To produce other pharmaceuticals in this species, an isolate completely devoid of β-lactam antibiotics was needed. Deleting all penicillin biosynthetic genes in a high producing strain led to such a host (15). To test whether the deletions had any adverse effect on secondary metabolite production potential, we reintroduced the biosynthetic genes, resulting in the recovery of penicillin production (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…P. chrysogenum is well known for β-lactam production, but this is an undesirable feature when producing other pharmaceuticals (29). Therefore, we used a variant in which the β-lactam biosynthetic genes are removed (15), essentially putting into practice the suggestion made by Jami et al (30) to use P. chrysogenum for other biotechnological purposes. Reintroduction of the penicillin biosynthetic genes proved that all capabilities were retained in this mutant, and introducing the compactin cluster demonstrated that beneficial mutations are not restricted to a single compound of interest but have general advantages for production of secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations